Resuscitation of the Ischaemic Brain - Murthy, TVSP; Prabhakar, Brig T; Sandhu, Kavita (Indian Journal of Neurotrauma, 2004)
‘Cerebral protection’ signifies strategies used to protect neural tissue from cellular events induced by deprivation of oxygen or glucose or both to the brain. Neurons are particularly susceptible to ischemic injury because they have a higher demand for energy and limited energy stores. Depletion of intrinsic central nervous system energy stores occurs within 2 to 4 minutes of anoxia. Protecting the brain from ischemia during neurosurgery is one of the most important concerns for Neuro anesthesiologists. Pharmacological brain protection may be employed to rest the brain while a temporary regional disruption in nutrient flow is expected to occur. Appropriate monitoring (EEG, evoked potentials, stump pressure, trans-cranial doppler) is needed to optimise therapy.Cerebral protection may be initiated prior to the occurrence of brain ischaemia. Certain prophylactic measures can interfere with the cascade of events triggered by the injury. Such a salutary effect may be achieved by reducing demand for energy (using barbiturates or hypothermia) or blocking mediators of ischemic injury. In designing the anaesthetic plan for patients at high risk of cerebral ischaemia (e.g, carotid endarterectomy, open heart procedures), it is useful to consider the relative degree of protection provided by various agents. Treating patients with neuroprotective agents after cardiac arrest or a focal ischemic insult may be consideration in improving overall neurological outcome. Focal ischemia encompasses stroke subarachnoid haemorrhage (SAH) and trauma. With few exceptions, animal studies have shown that therapeutic efficacy is lost if treatment is delayed more than one hour after impact. Sooner the neuroprotective drug is given, the better is the outcome.
Keywords: brain protection; calcium channel blockers; hypothermia propofol